Restricted vancomycin policy for staphylococcal late onset sepsis in a Portuguese neonatal intensive care unit - Margarida Roquette; Joana Antunes; Rosário Cancella-; Ana Tavares; Manuel Cunha (Publicaciones Permanyer, 2023)
Introduction: Sepsis is a major cause of morbimortality in newborns and Staphylococcus spp are responsible for most cases of lateonset sepsis. Our unit adopted a conservative policy, using flucloxacillin and gentamicin as first line therapy, switching to vancomycin if isolation of methicillinresistant Staphylococcus aureus or clinical deterioration. We aim to evaluate the efficacy of our practice. Methods: Analysis of staphylococcal lateonset sepsis (2011-2020) in a neonatal intensive care unit. Demographic, clinical presentation, treatment and outcome were analyzed. Asymptomatic infants were excluded; consecutive positive blood cultures in the same episode of sepsis were counted once. Results: Fifty nine cases of lateonset sepsis by Staphylococcus were found with 109 positive blood cultures. Median gestational age 31 weeks, median birth weight 1.435g. Clinical presentation: bradycardia (53%, n = 31), lethargy/irritability (51%, n = 30), "ill appearance" (42%, n = 25). Isolated agents: coagulase negative Staphylococci 73% (n = 43), Staphylococcus aureus 27% (n = 16) methicillin-resistant 15% (n = 9) and methicillin-sensitive 12% (n = 7). Empirical therapy with flucloxacillin and gentamicin instituted in 90% (n = 53) of cases; mean duration of treatment 11.4 days (SD ± 3.6). Switch for vancomycin in 28.3% of cases (n = 15). Vancomycin avoided in 66% (n = 39). Due to clinical improvement initial therapy was maintained in 84.4% (n = 27) cases of coagulase negative Staphylococci resistant to flucloxacillin. We had one death (methicillin-resistant Staphylococcus aureus treated with vancomycin from day one). Discussion: Our conservative policy was associated with low mortality, even if in vitro resistance. Conclusion: It seems to be a safe approach, with most of the newborns showing a good outcome and duration of therapy within the recommendations. These outcomes support a restrictive use of vancomycin, preventing the emergence of resistance.